Factors Associated With The Tendency Of Bullying Behavior In Adolescents At Smp Negeri 1 Mojoanyar Mojokerto District - Tabita Ruliyanti Erma; Yudha Laga Hadi Kusuma; Nurul Mawaddah; Lingga Kusuma Wardhani (Journal of Health Science Community, 2025)
Adolescence is a very important period, because it is a period of change from childhood to adulthood which includes mental, emotional and physical maturity. In this transition period, adolescents have many risks that may increase the number of juvenile delinquency and aggressive behavior, one of which is bullying, which is still rampant in several regions of Indonesia. The purpose of this study was to determine the factors associated with the tendency of bullying behavior in adolescents at SMP Negeri 1 Mojoanyar. This study used a cross-sectional design. The population in this study were 223 respondents with a sample of 143 respondents. The sampling technique used was probability sampling. Data were collected using a questionnaire of family communication patterns, school climate, peers, and bullying behavior tendencies. Data processing and analysis using chy square test. The results showed that most of the respondents who were at risk of bullying were male adolescents aged 14-16 years. The results obtained a p value of 0.000 < a 0.005 which means H1 is accepted, so there is a relationship between peers and the tendency of bullying behavior in adolescents at SMP Negeri 1 Mojoanyar, but the results of the study also obtained a p value of 0.427> α 0.005 which states that there is no relationship between family communication patterns and the tendency of bullying behavior in adolescents at SMP Negeri 1 Mojoanyar, and p value 0.214 > α 0.005 which states that there is no relationship between school climate and the tendency of bullying behavior in adolescents at SMP Negeri 1 Mojoanyar. The importance of increasing the knowledge and awareness of adolescents and parents related to bullying behavior needs to be considered and there needs to be rules applied at school related to bullying.